THE IMPACT OF THE SOCIAL DEMOGRAPHIC CHARACTERISTICS OF THE RURAL YOUNG FAMILY ON THE TERRITORIES’ DEVELOPMENT. A STUDY CASE - THE REPUBLIC OF BASHKORTOSTAN - Lyutsiya Mugtabarovna GAISINA; Yuri Nikolaevich DOROZHKIN; Gulnara Aydarovna IAKUPOVA; Albina Galirakhmanovna GAINANOVA; Elina Ildarovna GAINANOVA; El (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The article deals with the problem of impact of modern social cultural and economic factors upon the young rural family. The problems of these contradictory and complex impacts led to such negative phenomena as reduction of its size, the growth of divorces and the share of people who have never been married, the growth of unregistered unions and births, the decrease in the number of children, the weakening of intra-family communications, the destruction of value foundations, and others. The problem of the rural territories’ development becomes urgent as in the globalization and urbanization conditions the youth strives to leave the modern village which is characterized by the scarcity of the labor application spheres, a low income level, the underdevelopment of population social protection forms, the lack of possibilities and places for spending a spare time. The author’s view on the young family problems has been given. The sociological studies made it possible to analyze social demographic situation presupposing the population decrease in connection with the number and the youth share decrease, the birth rate reduction alongside with a gradual transfer to the European family model, the women education growth and the value orientation change of the rural youth will cause serious problems of the territories’ occupation and the traditional economic direction development-the agricultural industrial complex of the Republic of Bashkortostan. The statistics data and the studies’ analysis have defined the directions of the young rural family model improvement.